Mapping of the QTLs governing grain micronutrients and thousand kernel weight in wheat (Triticum aestivum L.) using high density SNP markers - Manjunath, Karthik Kumar; Krishna, Hari; Devate, Narayana Bhat; Sunilkumar, V. P.; Chauhan, Divya; Singh, Shweta; Mishra, C. N.; Singh, J. B.; Sinha, Nivedita; Jain, Neelu; Singh, Gyanendra Pratap; Singh, Pradeep Kumar (Frontiers in Nutrition, 2023)
Biofortification is gaining importance globally to improve human nutrition through enhancing the micronutrient content, such as vitamin A, iron, and zinc, in staple food crops like wheat. Improving the concentration of vitamins and minerals through biofortification in wheat reduces the problems of hidden hunger in bread-consuming parts of the world. The present study aims to identify the chromosomal regions governing the grain iron concentration (GFeC), grain zinc concentration (GZnC), and thousand kernel weight (TKW) using recombinant inbred lines (RILs), developed from a cross between HD3086 and HI1500. The experiment was conducted in four different production conditions at Delhi viz., control, drought, heat, and combined heat and drought stress. Under drought stress experiment was conducted at Indore. Genotyping was done using SNP markers from the 35k Axiom Breeder’s array. Grain iron and zinc content increased under heat and combined stress conditions, while thousand kernel weight decreased. Medium to high heritability with a moderate correlation between grain iron and zinc was observed. Out of 4106 polymorphic markers between the parents, 3407 markers were used for linkage map construction which spanned over a length of 14791.18 cM. QTL analysis identified a total of 32 chromosomal regions governing the traits under study, which includes 9, 11, and 12 QTLs for grain iron concentration, grain zinc concentration, and thousand kernel weight respectively. A QTL hotspot was identified on chromosome 4B which is associated with grain iron, grain zinc, and thousand kernel weight explaining the phenotypic variance of 29.28, 10.98, and 17.53 %, respectively. Similarly, common loci were identified on chromosomes 4B and 4D for grain iron, zinc, and thousand kernel weight. In-silico analysis of these chromosomal regions identified putative candidate genes that code for proteins such as Inositol 1,3,4-trisphosphate 5/6-kinase, P-loop containing nucleoside triphosphate hydrolase, Pleckstrin homology (PH) domains, Serine-threonine/tyrosine-protein kinase and F-box-like domain superfamily proteins which play role in many important biochemical or physiological process. The identified markers linked to QTLs can be used in MAS once successfully validated.